2011
DOI: 10.7205/milmed-d-10-00319
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Snoring and Sleep-Disordered Breathing Among Military Personnel

Abstract: With the possible implications for the military, greater attention with regards to SDB or OSAS is required, especially to its recognition and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…This may increase the risk of DIS ( 24 ), which was also a finding in this report. Other risk factors for sleep disturbances were also those expected from other studies, such as a having a history of asthma ( 12 ) and a high BMI ( 25 – 27 ).…”
Section: Discussionsupporting
confidence: 61%
“…This may increase the risk of DIS ( 24 ), which was also a finding in this report. Other risk factors for sleep disturbances were also those expected from other studies, such as a having a history of asthma ( 12 ) and a high BMI ( 25 – 27 ).…”
Section: Discussionsupporting
confidence: 61%
“…A study on the prevalence of snoring and sleep-disordered breathing among military personnel in the UK was conducted in 1300 personnel [ 6 ]. They also recruited subjects of different ranks and genders, and the percentage of females was low (11.3%), similar to that in our study (6.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Among these US military personnel, 70.9% returned from a combat within 12 months, and military personnel with comorbid insomnia and OSA were significantly more likely to meet the criteria for depression and PTSD [ 8 ]. In 1300 UK military personnel, the prevalence rates of snoring and OSA were 19.5 and 2.9% [ 6 ], respectively, and no study of OSA and snoring in the Thai military officer has been reported. Thus, the present study intends to investigate these aspects in the target group of the Royal Thai Army personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Weight, smoking, and alcohol use are all risk factors for sleep apnea. Sleep apnea is highly prevalent in MM with prevalence rates of 37.5% in active MM reported in 2005 [37, 38] and as high as 62.7% in a 2013 study of 110 MMs recently returned from combat [39]. …”
Section: Introductionmentioning
confidence: 99%
“…These challenges include communal sleeping, training, and field action that is highly alerting and does not allow for a “wind-down” period prior to sleep and psychologically unsettling events. A study of British soldiers found that 19.5% snored and this behavior can have a serious negative impact on the sleep of others in communal settings [38]. Additionally, the appropriate timing of daylight exposure needed for circadian regulation may not be possible.…”
Section: Introductionmentioning
confidence: 99%